Peningkatan Kapabilitas UMKM Binaan Rumah Kreatif Bogor Dalam Melakukan Analisa Laporan Keuangan - Yoyon Supriadi (Jurnal Abdimas Dedikasi Kesatuan, 2021)
Increasing the Capability of Micro, Small, and Medium Enterprises (UMKM) Assisted by Bogor Creative Houses in conducting report analysis is intended so that UMKM actors can analyze, evaluate and assess their business performance as well as make useful decisions to be able to make improvements and complete improvements independently of their business activities.This activity is designed systematically, easily and communicatively so that the trainees can easily accept and understand the material presented. In addition, this activity is designed openly so that participants are willing to convey the problems they face so that effective and appropriate ways can be found in accordance with the problems they face. Keywords: Financial Statement Analysis, Evaluation, Performance and Decisions